A afetividade nas práticas pedagógicas de alfabetização e letramento no ensino fundamental - COSTA, Carla Gabriela do Lago (2023)
This research aimed to show the importance of the applicability of affectivity in the pedagogical practices of literacy and literacy in the early years of elementary school. For this, a bibliographical research was carried out, where there was a survey of several works by important authors that deal with literacy and literacy and the relevance of affectivity for education and development, both cognitive and several other skills of children. Based on the analyses, we made some considerations regarding some existing issues and aspects regarding the teaching and learning of reading and writing and about the relationships of social interactions and affectivity in the development of children in Jean Piaget's conceptions, in which, from Based on the given considerations, we analyzed and correlated the value of social interactions and affectivity in teachers' practices for teaching children to read and write. Finally, we can consider that the process of literacy and literacy is quite complex, having several peculiarities to be considered in this process, thus, it is of great importance that teachers recognize and consider these various facets, in which affectivity will be paramount for the children's learning development.